Early Irish kingship - Finnegan, R (1960)
This is not a piece of original research. It is merely an attempt to see what an anthropologist, using the discipline of modern social anthropology, can make of the material that has already been published on pro-Conquest Ireland. The earlier of the chapters on Ireland are little more than a rewriting (and not , I hope, a misrepresentation) of recent specialist publications. The later sections (especially those concerned with the virtues of the kings, and the symbolism associated with Irish kingship) involve a certain amount of analysis that has not, so for as I know, been attempted before in quite the some form, though, as I think, all the main points on which it is supported have been made before by others. It arises in particular from the work of Domézil on Indo-European concepts of sovereignty, of Hocart on kingship, and, in part, from Myles Dillon's consideration of the concept of "Truth" in Irish literature. This being so, and considering also the purpose for which this is written (i.e. for social anthropologists), it would be both ludicrous and pretentious to include extensive quotations in the little known language of Irish. Many (not all) of the quotations given have been referred to in Irish. but they are consistently given here in English. I have not, however, been able to prevent several Irish words and phrases from creeping in. A brief glossary of the most constantly used Irish terms is included for ease of reference, though it has not been possible to standardise the spelling throughout.